Experiment and Simulation Study of Single Cylinder Diesel Engine Performance, Using Soybean Oil Biodiesel - Muhammad Rizqi Ariefianto; Aguk Zuhdi Muhammad Fathallah; Wolfgang Busse (Jurnal Teknik ITS, 2016)
Abstract— The most common fuel uses in the world is made from fossil. Fossil fuel is categorized as a non-renewable energy source. For that reason, there should be an alternative fuel to replace fossil fuel by using biodiesel and one of the stock comes from soybean bean. Before using the biodiesel made from soybean bean oil, there should be a research to find out the properties and the effect of biodiesel from soybean bean oil regarding the performance of the engine. The research can be conducted in experiment and simulation. The properties result of soybean oil biodiesel should be tested to confirm whether this biodiesel have meet the standard requirement of biodieselor not. This biodiesel sproperties are Flash Point value is 182 o C , Pour Point value is -7 o C, Density at 15 o C is 890 Kg/m3, Kinematic Viscosity at 40 o C is 5.58 (cSt), and Lower Heating Value is 42.27686 MJ/kg. The result from this research is the highest power from simulation is 9% higher than the experiment. The highest torque from the experiment is 37% lower than the simulation’s torque. Lowest SFOC from experiment is  28% lower than the simulation’s SFOC. Highest BMEP from simulation is 20% higher than the highest BMEP from experiment. The  highest thermal efficiency from experiment is 6% higher than the highest thermal efficiency from simulation. The engine performance result using soybean oil biodiesel is not better than the Pertamina Dex. For that reason, the use of this biodiesel is not suggested to substitute Pertamina Dex.